Magnetite Nanoparticles Induce Genotoxicity in the Lungs of Mice via Inflammatory Response - Yukari Totsuka; Kousuke Ishino; Tatsuya Kato; Sumio Goto; Yukie Tada; Dai Nakae; Masatoshi Watanabe; Keiji Wakabayashi (Nanomaterials, 2014)
Nanomaterials are useful for their characteristic properties and are commonly used in various fields. Nanosized-magnetite (MGT) is widely utilized in medicinal and industrial fields, whereas their toxicological properties are not well documented. A safety assessment is thus urgently required for MGT, and genotoxicity is one of the most serious concerns. In the present study, we examined genotoxic effects of MGT using mice and revealed that DNA damage analyzed by a comet assay in the lungs of imprinting control region (ICR) mice intratracheally instilled with a single dose of 0.05 or 0.2 mg/animal of MGT was approximately two- to three-fold higher than that of vehicle-control animals. Furthermore, in gpt delta transgenic mice, gpt mutant frequency (MF) in the lungs of the group exposed to four consecutive doses of 0.2 mg MGT was significantly higher than in the control group. Mutation spectrum analysis showed that base substitutions were predominantly induced by MGT, among which G:C to A:T transition and G:C to T:A transversion were the most significant. To clarify the mechanism of mutation caused by MGT, we analyzed the formation of DNA adducts in the lungs of mice exposed to MGT. DNA was extracted from lungs of mice 3, 24, 72 and 168 h after intratracheal instillation of 0.2 mg/body of MGT, and digested enzymatically. 8-Oxo-7,8-dihydro-2′-deoxyguanosine (8-oxodG) and lipid peroxide-related DNA adducts were quantified by stable isotope dilution liquid chromatography-mass spectrometry (LC-MS/MS). Compared with vehicle control, these DNA adduct levels were significantly increased in the MGT-treated mice. In addition to oxidative stress- and inflammation related-DNA adduct formations, inflammatory cell infiltration and focal granulomatous formations were also observed in the lungs of MGT-treated mice. Based on these findings, it is suggested that inflammatory responses are probably involved in the genotoxicity induced by MGT in the lungs of mice.